Contribution of Principal Leadership, Teacher Professionalism, and School Climate to the School Quality (Case Study Junior High School in Karanganyar Regency). - Prayitna, Sugeng (2012)
This research aims to determine four things. (1) Contribution of Principal Leadership for Schools Quality. (2) Contribution of Teacher Professionalism to the School Quality. (3) Contribution of School Climate on School Quality. (4) Contribution of Principal Leadership, Teacher Professionalism and School Climate jointly to School Quality. This research uses a quantitative approach. The research was conducted in the Junior High School in Karanganyar Regency 2011. School population in this study amounted to 51 schools and school samples amounted to 45 schools. Respondents in the research was the headmaster at throughout the school sample. The data was collected quesioner techniques. Techniques of data analysis using multiple linear regression analysis. statistics F test, t test statistics, and the coefficient of determination (R2). The research concluded that: (1) There is a significant contribution to the principal leadership on school quality. This is evidenced by the acquisition of 4.690 t test statistic is significant at = 0.05. (2) There is a contribution to the school quality of the teachers' professionalism. This is evidenced by the acquisition of the t test results of 4.111 are statistically significant at = 0.05. (3) There is a school climate contribute to the quality of schools. This is evidenced by the acquisition of the t test results of 2.113 are statistically significant at = 0.05. (4) There are contributions a principal leadership, teacher professionalism and school climate on school quality simultaneously. This is evidenced by the test results obtained model accuracy rates of 47.776 F statistic is significant at = 0.05. The results obtained coefficient of determination R2 rates for 0.761. It is understood that the principal‟s leadership, teacher professionalism, school climate and jointly determine the variability of the quality of junior high school in Karanganyar Regency about 76.1%. The other about 23.9% determined by other variables outside the model. Regression equation obtained in this research is Y = -4.318 + 0.479X1 + 0.416X2 + 0.178X3. Positive signs on regression coefficients X1, X2, and X3 show a positive contribution, it mean that the higher leadership of the principal, teacher professionalism, school climate and the higher the quality of junior high schools in Karanganyar Regency.